2008
DOI: 10.1598/jaal.52.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Writer Identity and ESL Learners

Abstract: Using Critical Discourse Analysis, this article explores the writer‐identity of a college ESL student in order to understand how embedded ideologies and power relations shape understanding of writer identity. Using a poststructural and sociocultural perspective, the author takes a stand regarding the politics of language and the teaching of writing, especially as they relate to students whose racial, ethnic, cultural, and economic backgrounds vary from the dominant culture of school. The article suggests strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 8 publications
0
25
0
Order By: Relevance
“…The researchers concluded that David and Oscar were marginalized and excluded from the writing community. Fernsten's (2008) case study of college English language learners explored how embedded ideologies and power relations shaped the writers' identity. A process-oriented approach to writing instruction encouraged the language learners to represent their diverse cultural voices in their writing.…”
Section: Research On English Language Learners' Writer Identitymentioning
confidence: 99%
“…The researchers concluded that David and Oscar were marginalized and excluded from the writing community. Fernsten's (2008) case study of college English language learners explored how embedded ideologies and power relations shaped the writers' identity. A process-oriented approach to writing instruction encouraged the language learners to represent their diverse cultural voices in their writing.…”
Section: Research On English Language Learners' Writer Identitymentioning
confidence: 99%
“…In this course I chose the theme of immigration to infuse into the reading and writing because students should be able to express themselves and their identity in their writing (Fernsten, 2008). Instead of constantly feeling confined to an academic discourse that may not value student identity, Fernsten advocates including ''expressivist'' writing assignments to ''value what [ESOL students] know'' (p. 51).…”
Section: Procedures Relevant Themementioning
confidence: 99%
“…The key findings in the set of LED studies that drew on written texts ( N = 40) tended to coalesce around seven major themes, with a few of the studies generating findings with overlapping themes. These key themes included issues of social justice or equity relating to education in general or to teaching and learning among youths and adult learners, with the following categories of findings: Learning across social differences (Fernsten, ; Gebhard et al., ; Hammond, ; Hashimoto, ; Johnson, , ; Marshall & Toohey, ; Powell, ; Schieble, ) Transformations in learner identity (Chen, ; Fernsten, , ; Goulah, ; Menard‐Warwick & Palmer, ; R. Rogers, ; Schmidt & Whitmore, ) Curricular materials and discourses (Dennis, ; Glenn, ; Hashimoto, ; Marshall & Toohey, ; R. Rogers & Christian, ; Schieble, ; Schmidt, ; Taylor, ; P.A. Young, ) Transformations in teacher identity (Cahnmann, Rymes, & Souto‐Manning, ; Davison, ; Moin et al., ; van Rensburg, ) Power and agency variability within specific contexts and/or discourses (Anderson, ; Gibb, ; Marshall & Toohey, ; R. Rogers, ) Movement or lack of movement across social class or socioeconomic identities (Anderson, ; Dutro, ; Dworin & Bomer, ) Processes of assessment (Prins & Toso, ; Tuten, ) …”
Section: Resultsmentioning
confidence: 99%